STUDI KASUS TENTANG TRUANCY BEHAVIOR PADA PESERTA DIDIK KELAS VIII DI SMP NEGERI 13 PONTIANAK - Gusti, Dermawanti Setyo; Yuline, Yuline; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this study was to find out and study in depth about truancy behavior in class VIII students at SMP Negeri 13 Pontianak. The case subjects in this study were two class VIII students who often carried out truancy behavior at school. This research uses a descriptive method with a qualitative approach in the form of a case study. Data collection techniques used were observation, interviews, documentation and home visits. While the data analysis technique uses case study steps which include problem identification, diagnosis, prognosis, treatment, evaluation and follow-up. In giving treatment, the researcher used two different counseling models to handle two students who did truancy behavior, namely using the Reality counseling model to handle the subject of case I and the Behavioral counseling model with assertive training techniques to handle the subject case II. Based on the results of the study, there were visible changes in the subjects of case I and case II after being given three meetings of treatment. The changes seen in the subject of case I included a reduction in the habit of skipping school, being more diligent in coming to school and a growing sense of responsibility in the subject of the case for his school life. Meanwhile, the changes seen in the subject of case II were being more diligent in coming to school, reducing the habit of skipping classes and being able to be assertive when refusing friends' invitations to skip classes